Heat flux and acoustic power in a T-shaped thermoacoustic system - Li, Shihuai (2015)
The present work considers a convection-driven T-shaped standing-wave thermoacoustic system. To gain insights on the conversion process of heat to sound and to study the nonlinear coupling between unsteady heat release and acoustic disturbances, thermodynamic analysis, numerical and experimental investigations are conducted. Three parameters are examined: (1) the inlet flow velocity, (2) heater temperature and (3) heat source location. Their effects on triggering limit cycle oscillations are first investigated in 2D numerical model. As each of the parameters is varied, the head-driven acoustic signature is found to change. The main nonlinearity is identified in the heat fluxes. To characterize the transient (growing) behavior of the pressure fluctuation, the thermoacoustic mode growth rate is defined and calculated. It is found that the growth rate decreases first and then ‘saturates’. Similar behavior is observed by examining the slope of Rayleigh index. Furthermore, the overall efficiency of converting the input thermal energy into acoustical energy is defined and calculated. It is found that the energy conversion efficiency can be increased by increasing the inlet flow velocity. To validate our numerical findings, a cylindrical T-shaped duct made of quartz-glass with a metal gauze attaching on top of a Bunsen burner is designed and tested. Supercritical bifurcation is observed. And the experimental measurements show a good agreement with the numerical results in terms of mode frequency, mode shape, sound pressure level and Hopf bifurcation behavior.